The Possible Role of Helicobacter pylori in Gastric Cancer and Its Management - Alfarouk, Khalid O.; Bashir, Adil H. H.; Aljarbou, Ahmed N.; Ramadan, AbdelRahman M.; Muddathir, Abdel Khalig; AlHoufie, Sari T. S.; Hifny, Abdelhamid; Elhassan, Gamal O.; Ibrahim, Muntaser E.; Alqahtani, Saad S.; AlSharari, Shakir D.; Supuran, Claudiu T.; et al. (Frontiers in Oncology, 2019)
Helicobacter pylori (HP) is a facultative anaerobic bacterium. HP is a normal flora having immunomodulating properties. This bacterium is an example of a microorganism inducing gastric cancer. Its carcinogenicity depends on bacteria-host related factors. The proper understanding of the biology of HP inducing gastric cancer offers the potential strategy in the managing of HP rather than eradicating it. In this article, we try to summarize the biology of HP-induced gastric cancer and discuss the current pharmacological approach to treat and prevent its carcinogenicity.